Rapid Production of Gene Replacement Constructs and Generation of a Green Fluorescent Protein-Tagged Centromeric Marker in Aspergillus nidulans - Yang, Lin (American Society for Microbiology, 2004)
A method to rapidly generate gene replacement constructs by fusion PCR is described for Aspergillus nidulans. The utility of the approach is demonstrated by green fluorescent protein (GFP) tagging of A. nidulans ndc80 to visualize centromeres through the cell cycle. The methodology makes possible large-scale GFP tagging, promoter swapping, and deletion analysis of A. nidulans.